Bantuan Teknis dalam Kajian Kelayakan Struktur Panggung Crocodile Attack Railing di Bali Safari Marine Park Gianyar-Bali - I Gusti Ngurah Eka Partama; Made Prarabda Karma; Putu Doddy Heka Ardana; Ni Kadek Astariani (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
PT. Jaya Graha Utama (PT. JGU) intends to rehabilitate the Crocodile Attack Railing Stage (CARS) at Bali Safari Marine Park (BSMP). Still, a reference has yet to be used to carry out this action. PT. JGU applied to the Faculty of Science and Technology, Ngurah Rai University (FST UNR) to conduct a structural studies and an FST UNR Community Service Team (CSFST) was formed with PT. JGU becomes a partner. CAFST activities are carried out using the Science and Technology Diffusion Method, from the survey stage to structural analysis. Concrete quality is determined by hammer test, reinforcement formation using the scanning rebar locator and structural analysis using SAP2000. The study's results recommend that the stage floor plate be replaced with a thickness of 10cm, the beam height dimensions be increased by 10cm to 15x40cm, 25x45cm, the addition of a 35cm diameter column at the base of the stage, and other columns remain. The study results and recommendations are compiled in books and files. The study results documents are very important in carrying out CARS rehabilitation measures at BSMP.